2003
DOI: 10.1080/1071576031000083116
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Oxidation Products, Antioxidant Markers, Antioxidant Capacity and Lipid Patterns in Plasma of Patients Affected by Papillon-Lefèvre Syndrome

Abstract: Papillon-Lefèvre syndrome (PLS) is an uncommon disease. Less than 300 cases have been described. PLS is characterized by the association between palmar plantar hyperkeratosis (PPK) and severe precocious periodontitis that results in the premature loss of both the primary and secondary dentitions. It is known that periodontitis (PE), the destructive phase of periodontal disease, is a multifactor phenomenon involving a variety of molecular species, among them free radicals and reactive oxygen species (ROS). Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…It has been reported that the concentrations of PUFA are reduced but those of monoenoic acids such as oleic acid (18:1) and palmitoleic acid (16:1) increase to compensate for the oxidative loss of PUFA under various conditions of oxidative stress. 20 Such changes in the plasma were, for example, observed in patients with adult respiratory distress syndrome, 21 multiple sclerosis, 22 Papillon-Lefevre syndrome, 23 and in newborn babies. 16 Similarly, they were noted in Long Evans Cinnamon (LEC) rats, 14 an animal model of hepatic cancer and Wilson's disease, and in rats with carbon tetrachloride poisoning.…”
Section: Resultsmentioning
confidence: 96%
“…It has been reported that the concentrations of PUFA are reduced but those of monoenoic acids such as oleic acid (18:1) and palmitoleic acid (16:1) increase to compensate for the oxidative loss of PUFA under various conditions of oxidative stress. 20 Such changes in the plasma were, for example, observed in patients with adult respiratory distress syndrome, 21 multiple sclerosis, 22 Papillon-Lefevre syndrome, 23 and in newborn babies. 16 Similarly, they were noted in Long Evans Cinnamon (LEC) rats, 14 an animal model of hepatic cancer and Wilson's disease, and in rats with carbon tetrachloride poisoning.…”
Section: Resultsmentioning
confidence: 96%
“…A previous study reported that plasma concentrations of PUFA decreased while those of monoenoic acids, such as oleic acid (18:1) and palmitoleic acid (16:1), increased to compensate for the oxidative loss of PUFA under various conditions of oxidative stress. 24 Such changes were observed in patients with adult respiratory distress syndrome, 25 multiple sclerosis, 26 Papillon-Lefevre syndrome, 27 and in newborn babies. 28 We recently observed that an elevation of plasma FFA levels and the contents of 16:1 and 18:1 in total FFA (%16:1 and %18:1, respectively) was induced by 2-hour occlusion-reperfusion of the middle cerebral artery in rats and that this change was attenuated by the administration of a free radical scavenger drug, edaravone.…”
Section: Oxidative Stress In Juvenile Fmmentioning
confidence: 96%
“…Several studies have demonstrated an increase in products of oxidative damage in peri pheral blood from persons with periodontitis compared with control individuals (Battino et al, 2001;Montebugnoli et al, 2004;Baltacioglu et al, 2008). Moreover, it is evidence of a decreased anti-oxidant capacity in persons with periodontitis, evaluated by different assays (Chapple et al, 2002Battino et al, 2003;Brock et al, 2004;Panjamurthy et al, 2005;Baltacioglu et al, 2006;Akalin et al, 2007;Konopka et al, 2007;Zilinskas et al, 2007).…”
Section: Resistin and Periodontitismentioning
confidence: 99%